Legacy of salmon-derived nutrients on riparian soil chemistry and soil fertility on the Central Coast of British Columbia, Canada - Larocque, Allen; Simard, Suzanne Winette (Frontiers in Forests and Global Change, 2023)
Soils from Haíɫzaqv (Heiltsuk) Nation territory on the Central Coast of British Columbia, Canada, were sampled to examine the long-term effects of salmon-derived nutrient subsidy on soil chemistry. A total of 20 soil chemical properties were assessed via two sampling methodologies: first, across 23 watersheds representing a regional gradient of salmon density (kg of salmon per meter of stream reach per year); and second, at four sites above and below waterfalls that blocked salmon migration. At each sampling point, soil material at two depths was collected: shallow soil and forest floor (0-5 cm), and deeper soil that was mostly organic in nature (10-15 cm). The abundance and species of moss, herbs, shrubs, and trees were also measured as covariates. A constrained multivariate analysis (partial RDA) on the regional gradient showed salmon density, the moss community, and the shrub community to be significant factors related to soil chemistry. Similarly, being above or below the waterfall, the moss community, and the tree community were significant in the waterfall comparison. Generalized linear mixed models along regional salmon density gradient showed an increase in nitrate (NO3-) correlated with salmon inputs (P<0.05), and moderately significant (P<0.1) increases in ammonium (NH4+), phosphorus (P), aluminum (Al), and copper (Cu). Net cation exchange capacity (CEC) did not change; however, magnesium (Mg) significantly decreased along these gradients (P<0.05), while sodium (Na) had a declining tendency and calcium (Ca) had an increasing tendency. Being below salmon-blocking waterfalls or the salmon density below falls was a factor in higher total nitrogen, nitrate, ammonium, phosphorus, total sulfur (S), magnesium, and sodium concentrations; below falls sites also had lower pH and aluminum. Exploratory analysis of the regional gradient data using a random forest model examined the importance of 19 covariates, representing vegetation, coarse woody debris, salmon density, distance from the stream, and soil depth. This apportioned high importance to soil depth, the moss community, the shrub community, salmon density and distance from the stream. These results show that salmon inputs are correlated with a number of changes in recipient soils, and these are consistent with an interpretation of improved fertility at these sites.